Crystallizing Membrane Proteins in Lipidic Mesophases. A Host Lipid Screen - CAFFREY, MARTIN (My University, 2011)
The default lipid for the bulk of the crystallogenesis studies performed to date using the cubic mesophase method is monoolein. There is no good reason however, why this 18-carbon, cis - monounsaturated monoacylglycerol should be the preferred lipid for all target membrane proteins. The latter come from an array of biomembrane types with varying properties that include hydrophobic thickness, intrinsic curvature, lateral pressure profile, lipid and protein makeup, and compositional asymmetry. Thus, it seems reasonable that screening for crystallizability based on the identity of the lipid creating the hosting mesophase would be worthwhile. For this, monoacylglycerols with differing acyl chain characteristics, such as length and olefinic bond position, must be available. A lipid synthesis and purification program is in place in the author's laboratory to serve this need. In the current study with the outer membrane sugar transporter, OprB, we demonstrate the utility of host lipid screening as a means for generating diffraction- quality crystals. Host lipid screening is likely to prove a generally useful strategy for mesophase- based crystallization of membrane proteins
PUBLISHED
Keywords: membrane protein structure;; OprB;; outer membrane proteins;; porin; screen; sugar transporter; X- ray crystallography